Sternoclavicular Joint Transfer in the Management of Temporomandibular Joint Ankylosis- A case report (Bangladesh Journal of Otorhinolaryngology, 2020)
Temporomandibular joint ankylosis is a clinical condition resulting in loss of jaw function and retardation of growth. The main objectives of the treatment for Temporomandibular joint ankylosis are to increase mouth opening, restore joint function, initiation of mandibular growth, improve the patient’s facial esthetic profile and prevent reankylosis. To release of ankylotic mass and gap is filled up with interpositional material. We reported a case of temporomandibular joint ankylosis in a 15 years old girl, whose treatment was done in the Department of Oral and Maxillofacial Surgery,Bangabondhu Sheikh Mujib Medical University, with sternoclavicular joint transfer which is very rare in our country and this was nearly fulfill treatment objective.Bangladesh J Otorhinolaryngol; April 2018; 24(1): 90-94